OP0207 B cell depletion increases regulatory t cells and ameliorates skin and lung fibrosis in a bleomycin-induced systemic sclerosis model mouse. (15th June 2017) - Numajiri, H; Yoshizaki, A; Fukasawa, T; Ebata, S; Asano, Y; Sato, S
Abstract : Background: B cells play a critical role in systemic autoimmunity and disease expression through various functions such as cytokine production and induction of other immune cell activation. Recently, some clinical studies have shown that the efficacy of B cell depletion therapy with rituximab, a chimeric monoclonal antibody against human CD20, in systemic sclerosis (SSc) patients. However, it still remains unclear why B cell depletion can be an effective treatment for SSc. Objectives: The purpose of this study is to assess the role of B cell depletion in SSc. We evaluated the skin and lung fibrosis of bleomycin (BLM)-induced SSc model mice treated with B cell depletion. Furthermore, we investigated the effect of B cell depletion on T cell cytokine profile. Methods: To generate BLM-induced SSc model mice, 300 μg of BLM was injected subcutaneously into the shaved backs of the C57BL/6 mice every other day for 4 weeks. Anti-mouse CD20 monoclonal antibodies, which can deplete mouse B cells, were also injected every 2 weeks from 2 weeks later starting BLM treatment. After 4 weeks of BLM treatment, skin and lung fibrosis were assessed histopathologically. T cells and B cells were isolated from spleen using magnetic cell sorting system. Purified T cells (5x10 5 cells) were cultured with B cells (5x10 5 cells) in the presence of phorbol 12-myristate 13-acetate, ionomycin, and anti-CD3/CD28 antibodies. Cytokine expressions in the fibrotic skin and lung were quantified by real-time polymerase chain reaction. Cytokine production of T cells and B cells were analyzed by flow cytometric analysis. Results: Dermal thickness and lung fibrosis score increased in BLM-treated mice compared with phosphate buffer saline (PBS)-treated control mice. Frequencies of interleukin (IL)-10 producing splenic B cells significantly decreased in BLM-treated mice compared with PBS-treated mice, while IL-6 producing B cell frequencies increased. Moreover, interferon (IFN)-γ, IL-4, or IL-17 producing T cell frequencies increased in BLM-treated mice. There were no significant differences in regulatory T cell frequencies between BLM-treated and PBS-treated mice. B cell depletion increased IL-10 producing regulatory T cell frequencies in BLM-treated mice. By contrast, frequencies of IFN-γ, IL-4, or IL-17 producing T cells were significantly decreased by B cell depletion in BLM-treated mice. In addition, fibrogenic cytokine mRNA expression levels of skin and lung decreased in BLM-treated mice with B cell depletion. To assess the role of B cells on T cell cytokine production, purified splenic B cells from BLM- or PBS-treated mice were cultured with naive T cells. T cells which were cultured with B cells from BLM-treated mice produced greater amounts of INF-γ, IL-4, and IL-17 than those cultured with PBS-treated mouse B cells. By contrast, B cells from PBS-treated mice induced a higher amount of IL-10 production from T cells than those from BLM-treated mice. Conclusions: B cell depletion inhibited skin and lung fibrosis in BLM-treated mice. Furthermore, B cell depletion increased regulatory T cell frequencies in BLM-treated mice, though INF-γ, IL-4, and IL-17 producing T cell frequencies were decreased by B cell depletion. These results suggest that B cell depletion alters T cell cytokine profile, which results in inhibition of fibrosis in this model. Disclosure of Interest: None declared